Способ устранения Гронинг-эффекта и эффекта экранирования при двойном боковом каротаже - Миронцов, Н.Л. (Доповіді НАН України, 2011)
Запропоновано засiб позбавлення вiд Гронiнг-ефекту та ефекту екранування при подвiйному бiчному каротажi, який засновано на змiнi режимiв живлення, вимiру та введення двох додаткових електродiв у зондову частину апаратури. Показано, що цi змiни значно зменшують вплив вмiсних пластiв на результат каротажу. Наведено приклад порiвняння синтетичних кривих класичного подвiйного каротажу та запропонованої апаратури. A method to eliminate the Groningen effect and the shielding effect at the double lateral logging is proposed. The method is based on changing the power supply regime, the measurement, and introducing two additional electrodes in the probing part of an equipment. It is shown that these changes reduce considerably the influence of enclosing strata on results of logging. The example of comparison between the synthetic logging curves of the classical double lateral logging and ones obtained with the proposed equipment is given.